Peace and conflict studies research: A qualitative perspective - Klein, Mike (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Peace and conflict studies research: A qualitative perspective, edited by Robin Cooper and Laura Finley, Charlotte, Information Age Publishing, 2014, 219 pp., US 45.99 (softcover), ISBN 978-1-62396-1.